Production of Karanja Methyl Ester from Crude Karanja Oil Using Meretrix Lyrata Synthesised Active Cao Catalyst - Harreh, Dewi; Saleh, A.A.; Reddy, A. N.R.; Hamdan, S.; Charyulu, K. (Universiti Malaysia Pahang, Malaysia, 2018)
Active calcium oxide catalyst was synthesised from Meretrix Lyrata (M.Lyrata) following calcination-hydration-dehydration technique. The catalytic feasibility of synthesised CaO was investigated in the production of Karanja methyl ester (KME) from crude Karanja oil (CKO). KME was synthesised through esterification using H2SO4 followed by transesterification utilising CaO in a two-step reaction process of CKO and methanol. The M.Lyrata shells were calcined at 900 ℃ and the catalyst samples were characterised using FTIR, SEM, PSA, and BET-BJH spectrographic techniques. A maximum fatty acid methyl ester (FAME) conversion of 97.3 % was obtained at optimum reaction conditions including methanol-to-oil ratio of 12:1, catalyst concentration of 2 wt.%, reaction temperature of 58 ℃ and reaction time of 2 hrs. In a comparative study with commercial CaO, M.Lyrata showed a higher catalytic activity. The catalyst reusability experiments ascertaining reusability of CaO up to four reuse cycles had shown good efficiency. The economic comparative study confirms that CaO derived from M.Lyrata can be used as an alternative and feasible catalyst for biodiesel production. The KME fuel properties complied to EN-14214 biodiesel fuel standards.